Pengaruh Kombinasi Ekstrak Carica Papaya dan Propolis Terhadap Peningkatan Trombosit - Widya Ningrum Lobang, Eka; Maharani Putri, Icha; Hanafi, Zidhan; Widhiyastuti, Endang (Jurnal Farmasi (Journal of Pharmacy), 2020)
to tearing of the skin, causing bleeding. If a person's platelet level <150,000, it’s called thrombocytopenia. Papaya leaves have a content to increase platelets. Propolis can be used as an anti-inflammatory drug because of the presence of CAPE and quertecin which play a role in suppressing T cell activity. CAPE is able to inhibit NF-kB and stimulant IL-2 which stimulates the work of T cells. This study aims to determine whether there is an effect of giving a combination of papaya leaf extract and propolis in increasing platelets. This study used a literature study method where the data used come from research reports, theses or scientific journals both national and international in the last 10 years related to the effect of papaya leaf extract on increasing platelets. Previous research has shown there is an effect of papaya leaf extract on the increase in platelet count (p 0.00004). Previous research has also mentioned that propolis contains a variety of components, such as flavonoids and alkaloids. Flavonoids in propolis are able to support the performance of papaya leaf extract in increasing the number of platelets. The conclusion in this study was that the papaya leaf extract was effective enough to help increase the platelet count. The combination of papaya leaf extract and propolis extract can help reduce inflammation.